Commitment to Work and its Relationship with Organizational Culture Mediated by Satisfaction - Silva, Lindomar Pinto; Castro, Miguel Angel Rivera; Dos-Santos, Marcos Gilberto; Neto, Pedro José Lima (Review of Business Management, 2018)
Purpose – The objective of this study is to analyze the mediating effect of satisfaction on the relationship between organizational culture and commitment at work. Design/methodology/approach – This paper adopts a quantitative and descriptive approach, applying an online questionnaire to employees of a public development bank operating in the Northeast of Brazil. The analysis method involved the use of structural equations modeling. Findings – The main results indicate that job satisfaction plays an important role in employee commitment, mediating the positive influence of organizational culture on commitment to work in its affective, instrumental, and normative dimensions in adhocratic cultures, and on affective commitment in clan cultures. They also indicate that satisfaction is a direct predictor of organizational commitment in the same way it mediates the relationship between culture and commitment. Originality/value – This paper contributes to increasing the theoretical knowledge about the relationships established between culture, satisfaction, and commitment. For the area of people management, this knowledge can favor organizational performance, allowing managers to act more accurately in each of these constructs.